Hamstring and quadriceps muscle strength in youth to senior elite soccer: a cross-sectional study including 125 players - Ishøi, L.; Krommes, K.; Nielsen, M. F.; Thornton, K. B.; Hölmich, P.; Aagaard, P.; Penalver, J. J. J.; Thorborg, K. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Increasing age, high quadriceps strength, and low hamstring muscle strength are associated with hamstring strain injury in soccer. The authors investigated the age-related variation in maximal hamstring and quadriceps strength in male elite soccer players from under-13 (U-13) to the senior level.